The Mechanics of Speed: A Systematic Literature Review on Athletic Sprint Techniques - Rumini; Adi S; Kusuma, Donny Wira Yudha (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to collect and analyze findings from research on athletic sprinting techniques through a biomechanics approach to provide an in-depth understanding of effective technique and biomechanical factors that influence sprint performance. Materials and methods. This review inquiry adhered to the PRISMA guidelines for systematic reviews and meta-analyses. The studies should have been published between January 2020 and August 2025, which encompassed the previous five years. The following keywords were used in the search process: Techniques for Athletic Sprinting. The search was conducted using the ScienceDirect database. Results. The search process showed the following results: set position — 2 articles, hip angle — 3 articles, shorter time — 2 articles, fascicle length — 1 article, knee flexor — 3 articles, and hamstring length — 2 articles. Conclusions. The center of mass and contact time along with force application to the back block are critical toacceleration. Muscle properties, such as fascicle length, and joint motion (ankle, hip, and BCM), in addition to trunk, knee, and hip angles, define sprint mechanics.